Produksi organic preservative dan solid biofuel dari hydrothermal treatment tongkol jagung dengan variasi temperatur - Haidar Ali; Ahmad Tawfiequrrahman Yuliansyah (Jurnal Rekayasa Proses, 2016)
Corn is one of staple food and influential commodity driving Indonesia’s economy. Indonesia currently produces as high as 19 million tons of corn which contains 50% of biomass in the form of cob. Waste from harvesting and consumption of corn, namely, corn cob (CC) is left as waste. This CC is actually a sustainable, easily accessible, and renewable biomass energy source as an alternative to Indonesia’s depleting fossil fuel reserves. Hydrothermal treatment is a conversion method that has some consequential advantages compared to other methods; e.g. the ability to treat high-moisture biomass like CC and the possibility to use lower temperature. This research aims to produce and characterize liquid and solid fuel subsequent to hydrothermal treatment of CC obtained from Sleman, Yogyakarta. After size reduction, fine particles were mixed with water to form slurry. Slurry was heated in an autoclave for hydrothermal treatment at initial pressure of 2.0 MPa and was held for 200 °C, 240 °C, and 270 °C in 30 minutes. The solid and liquid products were then separated. Liquid was analyzed using GC-MS and solid by using AAS. The result showed that, in comparison to raw material, solid product had higher carbon content which resulted in the increase of calorific value of the solid biofuel. The calorific value of solid product ranged from 19,59 -22,02 MJ/kg or 20,93-35,87% higher than raw materials and 4-17% higher than average coal used in Indonesia. Major component in liquid product are N, N-dimethyl formamide, furfural, and phenolic compound, with benzoic acid present as minor component. The potential of liquid products as organic preservatives are examined by testing the tenacity of wood against termite according to ASTM D3345-74 standard method. Result showed that liquid product were effective in exhibiting termiticidal activity and temperature 200 °C showed the optimum condition.